Synchronized HIV assembly by tunable PIP2 changes reveals PIP2 requirement for stable Gag anchoring - Mücksch, Frauke; Laketa, Vibor; Müller, Barbara; Schultz, Carsten; Kräusslich, Hans-Georg (eLife, 2017)
PI(4,5)P2 plays a much broader role during the HIV-1 particle assembly process than assumed; it is indispensable not only for recruitment of Gag to the plasma membrane but also for the maintenance of Gag assemblies.